2022
DOI: 10.1111/bjso.12580
|View full text |Cite
|
Sign up to set email alerts
|

Who is expected to make contact? Interpretative repertoires related to an intergroup encounter between Finnish majority mothers and immigrant mothers

Abstract: Although the benefits of contact for positive intergroup relations are widely acknowledged, less is known about how group members construct the agency and responsibility of contact participants in intergroup encounters. Using critical discursive psychology, we analysed the interpretative repertoires that Finnish majority mothers (N = 13) and mothers with an immigrant background (N = 10) used when talking about a hypothetical intergroup encounter among Finnish and immigrant mothers in a ‘family café’ (a group f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The power imbalance inherent in institutional contact seems easily to frustrate the intergroup contact opportunity, as the professionals apply a dual approach of care and control in their dealings with service users (Bendixsen & Danielsen, 2020;Erstad, 2018), meanwhile representing the majority ethnic group. In peer contact (e.g., between mothers; see Riikonen et al, 2023), a shared identity may be employed to facilitate contact, but this seems unlikely in institutional contact because of power and role differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The power imbalance inherent in institutional contact seems easily to frustrate the intergroup contact opportunity, as the professionals apply a dual approach of care and control in their dealings with service users (Bendixsen & Danielsen, 2020;Erstad, 2018), meanwhile representing the majority ethnic group. In peer contact (e.g., between mothers; see Riikonen et al, 2023), a shared identity may be employed to facilitate contact, but this seems unlikely in institutional contact because of power and role differences.…”
Section: Discussionmentioning
confidence: 99%
“…The power imbalance inherent in institutional contact seems easily to frustrate the intergroup contact opportunity, as the professionals apply a dual approach of care and control in their dealings with service users (Bendixsen & Danielsen, 2020; Erstad, 2018), meanwhile representing the majority ethnic group. In peer contact (e.g., between mothers; see Riikonen et al, 2023), a shared identity may be employed to facilitate contact, but this seems unlikely in institutional contact because of power and role differences. Prior social psychological contact research studying group hierarchy and intergroup power relations has showed that a typical mismatch between advantaged and disadvantaged groups is their differing interest to discuss power disparities; the advantaged groups tend to have less interest to discuss group‐based power and are more willing to find commonalities among groups to maintain the status quo (Saguy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mothers' daily life with young children is often located close to home, the local community of mothers is perceived as a potential source of company and social support (Strange et al, 2015; Varin et al, 2020; Wood et al, 2011). Although motherhood is found to increase interest in social connectedness with other local mothers (Riikonen et al, 2022; Seppälä et al, 2021), studies report diverse lived experiences among mothers.…”
Section: Introductionmentioning
confidence: 99%